The Peroxidative Cleavage of Kaempferol Contributes to the Biosynthesis of the Benzenoid Moiety of Ubiquinone in Plants. Issue 12 (14th November 2018) - Soubeyrand, Eric; Johnson, Timothy S.; Latimer, Scott; Block, Anna; Kim, Jeongim; Colquhoun, Thomas A.; Butelli, Eugenio; Martin, Cathie; Wilson, Mark A.; Basset, Gilles J.
Abstract : Genetic and biochemical evidence shows that Arabidopsis and tomato can derive the ubiquinone precursor 4-hydroxybenzoate from the B-ring of kaempferol. Abstract: Land plants possess the unique capacity to derive the benzenoid moiety of the vital respiratory cofactor, ubiquinone (coenzyme Q), from phenylpropanoid metabolism via β-oxidation of p -coumarate to form 4-hydroxybenzoate. Approximately half of the ubiquinone in plants comes from this pathway; the origin of the rest remains enigmatic. In this study, Phe-[ Ring - 13 C6 ] feeding assays and gene network reconstructions uncovered a connection between the biosynthesis of ubiquinone and that of flavonoids in Arabidopsis ( Arabidopsis thaliana ). Quantification of ubiquinone in Arabidopsis and tomato ( Solanum lycopersicum ) mutants in flavonoid biosynthesis pinpointed the corresponding metabolic branch-point as lying between flavanone-3-hydroxylase and flavonoid-3′-hydroxylase. Further isotopic labeling and chemical rescue experiments demonstrated that the B-ring of kaempferol is incorporated into ubiquinone. Moreover, heme-dependent peroxidase activities were shown to be responsible for the cleavage of B-ring of kaempferol to form 4-hydroxybenzoate. By contrast, kaempferol 3-β-d -glucopyranoside, dihydrokaempferol, and naringenin were refractory to peroxidative cleavage. Collectively, these data indicate that kaempferol contributes to the biosynthesis of a vital respiratory cofactor, resulting in an extraordinary metabolic arrangement where a specialized metabolite serves as a precursor for a primary metabolite. Evidence is also provided that the ubiquinone content of tomato fruits can be manipulated via deregulation of flavonoid biosynthesis.